Yang-Mills action from open superstring field theory - Berkovits, Nathan [UNESP]; Schnabl, Martin (Springer Nature, 2003)
We calculate the effective action for nonabelian gauge bosons up to quartic order using WZW-like open superstring field theory. After including level zero and level one contributions, we obtain with 75% accuracy the Yang-Mills quartic term. We then prove that the complete effective action reproduces the exact Yang-Mills quartic term by analytically performing a summation over the intermediate massive states. © SISSA/ISAS 2003.
Keywords: String Field Theory; Superstrings and Heterotic Strings